The Effect Of Career Development, Mentoring, And Training On Nurses Job Engagement: The Moderating Role Of Organizational Support - Agustin Linda Astuti; Hwihanus, Hwihanus (Sean Institute, 2024)
This study aims to analyze the influence of career development, mentoring, and training on nurses' work engagement, and examine the moderating role of perceived organizational support in this relationship. This research is based on the premise that nurse work involvement is an important aspect in improving hospital organizational performance. Factors such as clear and structured career development, effective mentoring, and well-planned training are hypothesized to have a positive influence on nurses' work engagement. However, this study also considers that not all nurses will respond to these factors in the same way, and perceived organizational support may moderate these relationships. This research used a quantitative approach and was conducted in a hospital context. It is hoped that the research findings will provide insight for hospital management in designing strategies to increase nurses' work involvement. This research contributes to the existing literature on factors influencing nurses' work engagement and the role of organizational support in this context.